A New Technique for Placement of Blocking Screws and its Mechanical Effect on Stability of Tibia Fractures with Distal Fragments after Insertion of Small‐Diameter Intramedullary Nails. Issue 7 (1st October 2021) - Zhang, Cong‐ming; Sun, Liang; Wang, Qian; Huang, Qiang; Lin, Hua; Duan, Ning; Zhang, Chen‐chen; Ma, Teng; Xue, Han‐zhong; Zhang, Kun; Li, Zhong
Abstract : Objective: To design a novel blocking screws (BSs) geometry and insertion method to treat distal tibia fracture with nailing and comparison of mechanical properties of novel and traditional screws. Methods: Twenty‐one synthetic left tibiae were sectioned to obtain 21 distal segments measuring 55 mm. Intramedullary (IM) 9‐mm tibial nails were advanced to 6 mm from the ankle joint. Two transverse and one anterior–posterior (AP) locking screws were inserted. Both medial–lateral (ML) BSs were placed 10 mm from the topmost interlocking screw. A custom‐made jig assisted in placing the novel and traditional BSs. The time spent in placing each BS was recorded. All the samples were repaired with an IM nail and without BSs, with two traditional BSs, and with two novel BSs. An initial loading from −150 to +150 N was applied to specimens in the ML direction at 185 mm from the nail end, followed by cyclic loading of the same for 10, 000 cycles with failure‐to‐test loading of 350 N in the ML direction. The maximum displacement was measured at 80 mm from the nail end and recorded under initial loading. The damage of two kinds of BSs to the nail was recorded. Results: Compared with average 5.21 min of the time of placing a traditional BS, the time spent in positioning a novel BS on the fracture model was 2.53 min. In the distal bone–implant constructs (BICs), the addition of traditional BSs decreased the maximum displacement of the BICs by 26.2%. The addition of the novel BSs decreased the displacement by 28.9%. All constructs survived 10, 000 cycles without hardware deformation. The failure rate of the control group was significantly greater than that of the traditional group; however, the novel group was similar to the traditional group. The damage of the traditional BS to the nail was greater than that of the novel one. Conclusions: The novel and traditional BSs are comparably effective for increasing the primary mechanical stability of distal metaphyseal fractures after nailin. However, compared to the placement of a traditional BS, implanting a novel BS took more less time and caused less damage to the nail. Additionally, the most obvious advantage of the novel BS design and insertion technology was that the pressure and distance between it and the IM nail could be controlled by rotating the screw. These advantages of the novel BS will be beneficial for clinical application. Abstract : This study introduces a new blocking screws (BSs) structure and compares the mechanical stiffnesses of novel and traditional BSs using a distal tibial fracture segment model treated with intramedullary nails. the most obvious advantage of the novel BS design and insertion technology was that the pressure and distance between it and the IM nail could be controlled by rotating the screw, which helped to shorten the adjustment time and reduce the occurrence of new fractures. By mechanical test, this study concluded that the stiffnesses of the novel and traditional BSs are equal.